2007
DOI: 10.1111/j.1468-1293.2007.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of dried spots and of different storage conditions of plasma for HIV‐1 RNA quantification

Abstract: ObjectivesThe aim of the study was to evaluate the use of dried plasma spots to determine HIV-1 RNA viral loads. MethodsThe viral loads of 30 liquid plasma samples were compared with those of corresponding dried plasma spots on filter paper (DPS-FP) and in tubes (DPS-T), both of which were left for 7 days at 22 1C. Also, 10 liquid plasma samples with detectable viral load were stored at 4, 22 or 37 1C for 7 days and five further liquid plasma samples were air-dried for up to 54 h to assess the effects of tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 12 publications
1
42
0
Order By: Relevance
“…However, it has been reported that samples can maintain their HIV-1 RNA concentrations for at least 14 days at 5°C and around 3 years at Ϫ20°C (14,16). Amellal and colleagues also demonstrated that 1 week of storage of plasma specimens at 4, 22, and 30°C did not significantly affect HIV-1 RNA viral load levels (3,4). In contrast, they obtained reduced median HIV RNA concentrations for samples stored at 37°C.…”
Section: Discussionmentioning
confidence: 94%
“…However, it has been reported that samples can maintain their HIV-1 RNA concentrations for at least 14 days at 5°C and around 3 years at Ϫ20°C (14,16). Amellal and colleagues also demonstrated that 1 week of storage of plasma specimens at 4, 22, and 30°C did not significantly affect HIV-1 RNA viral load levels (3,4). In contrast, they obtained reduced median HIV RNA concentrations for samples stored at 37°C.…”
Section: Discussionmentioning
confidence: 94%
“…Since viral load testing requires specialized facilities and experienced personnel, alternative strategies have been explored. Recent reports have suggested that DBS may be suitable for use for the testing of HIV RNA levels, although most studies have so far examined only small sets of samples (1,2,25,32,34). Both the reliability and the sensitivity of tests that use DBS compared to those that use plasma have been matters of concern.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of dried blood spots (DBS) is increasingly being considered as an alternative that can be used to overcome the troubles inherent to the testing of plasma. Patient's blood placed on DBS can be shipped at room temperature to specialized reference laboratories, where the specimens may be subject to HIV RNA quantitation (1,2,3,8,11,22), HIV subtyping, and/or drug resistance testing (5,15,19,28). DBS have also been successfully used to assist with the confirmation of a diagnosis of HIV infection (10,18,27), measurement of CD4 counts (23), and even analysis of antiretroviral drug levels (17).…”
mentioning
confidence: 99%
“…Dried blood spots (DBS) may be an interesting alternative to plasma for periodic VL testing (1,5,7,9,12,23). DBS can be easily collected and stored without being frozen or refrigerated (2,17,22). Several studies have demonstrated the feasibility of DBS as a specimen type for VL testing using different methodologies, although limitations in terms of sensitivity and stability have been noted (3,5,9,10,12,16).…”
mentioning
confidence: 99%